A randomized controlled trial of cognitive therapy, a self-help booklet, and repeated assessments as early interventions for posttraumatic stress disorder. - Ehlers, A; Clark, D; Hackmann, A; McManus, F; Fennell, M; Herbert, C; Mayou, R (2003)
BACKGROUND: It is unclear what psychological help should be offered in the aftermath of traumatic events. Similarly, there is a lack of clarity about the best way of identifying people who are unlikely to recover from early posttraumatic symptoms without intervention. OBJECTIVE: To determine whether cognitive therapy or a self-help booklet given in the initial months after a traumatic event is more effective in preventing chronic posttraumatic stress disorder (PTSD) than repeated assessments. DESIGN: Randomized controlled trial. Patients Motor vehicle accident survivors (n = 97) who had PTSD in the initial months after the accident and met symptom criteria that had predicted persistent PTSD in a large naturalistic prospective study of a comparable population. SETTING: Patients were recruited from attendees at local accident and emergency departments. INTERVENTIONS: Patients completed a 3-week self-monitoring phase. Those who did not recover with self-monitoring (n = 85) were randomly assigned to receive cognitive therapy (n = 28), a self-help booklet based on principles of cognitive behavioral therapy (n = 28), or repeated assessments (n = 29). MAIN OUTCOME MEASURES: Symptoms of PTSD as assessed by self-report and independent assessors unaware of the patient's allocation. Main assessments were at 3 months (posttreatment, n = 80) and 9 months (follow-up, n = 79). RESULTS: Twelve percent (n = 12) of patients recovered with self-monitoring. Cognitive therapy was more effective in reducing symptoms of PTSD, depression, anxiety, and disability than the self-help booklet or repeated assessments. At follow-up, fewer cognitive therapy patients (3 [11%]) had PTSD compared with those receiving the self-help booklet (17 [61%]; odds ratio, 12.9; 95% confidence interval, 3.1-53.1) or repeated assessments (16 [55%]; odds ratio, 10.3; 95% confidence interval, 2.5-41.7). There was no indication that the self-help booklet was superior to repeated assessments. On 2 measures, high end-state functioning at follow-up and request for treatment, the outcome for the self-help group was worse than for the repeated assessments group. CONCLUSIONS: Cognitive therapy is an effective intervention for recent-onset PTSD. A self-help booklet was not effective. The combination of an elevated initial symptom score and failure to improve with self-monitoring was effective in identifying a group of patients with early PTSD symptoms who were unlikely to recover without intervention.